Research progress of mycotoxins in edible vegetable oil - HUANG Changgang; YAN Zhaofeng; YANG Xin; YANG Dajin (Zhongguo shipin weisheng zazhi, 2023)
Mycotoxins have proven to be harmful substances to human health. Edible vegetable oils contain a variety of mycotoxins that are carcinogenic， mutagenic， and genotoxic to the human body. This paper comprehensively discusses the research progress on mycotoxins in edible vegetable oils， covering aspects such as their sources， harmful effects， detection methods， limit standards， pollution status， and pollution control.